2015
DOI: 10.1177/0021934715599424
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Increasing the Number of Black Men in Professional Psychology

Abstract: The underrepresentation of Black men in professional psychology represents a critical issue, but this topic has received relatively limited coverage in the extant literature. Given the complex challenges facing many Black communities, we contend that increasing the number of African American male professional psychologists represents one component of the multi-pronged plan to tackle these problems. However, there is a dearth of scholarship that explicitly highlights the potential contributions Black men can ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Currently, Black men are significantly underrepresented at all levels of the psychology pipeline. For the 2012 academic year Black men earned 1% of all doctoral degrees awarded in psychology, whereas Black women represented 5% of all newly minted psychologists (Beasley, Miller, & Cokley, ). As such, HBCU programs should be surveyed to determine if differences exist in mentoring and career trajectories of their male and female graduates.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, Black men are significantly underrepresented at all levels of the psychology pipeline. For the 2012 academic year Black men earned 1% of all doctoral degrees awarded in psychology, whereas Black women represented 5% of all newly minted psychologists (Beasley, Miller, & Cokley, ). As such, HBCU programs should be surveyed to determine if differences exist in mentoring and career trajectories of their male and female graduates.…”
Section: Discussionmentioning
confidence: 99%
“…Changing perceptions of Black male students among teachers is an important step. However, stakeholders have to continue to work together to recruit and retain more Black mental health practitioners and teachers (Beasley, Miller, & Cokley, 2015;Bristol & Goings, 2019). Considerable research highlights the disconnect between Black and White teacher's perceptions of Black students (Cherng & Halpin, 2016).…”
Section: Paving the Road To Wellness For Black Malesmentioning
confidence: 99%
“…Finally, due to the decade-long shortage of men in nursing and teaching, researchers have invested significant attention to examining these areas, whereas psychology has not received similar empirical attention. For example, our literature review found only one theoretical article (Beasley, Miller, & Cokley, 2015) and one empirical study (Isacco, Hammer, & Shen-Miller, 2016) on men in psychology. Unfortunately, prior research has not directly examined factors that contribute to the lower numbers in this female majority field or discussed the role career counselors can play in addressing this gender disparity in their work with boys and men.…”
Section: Purpose Of Current Studymentioning
confidence: 99%